2002
DOI: 10.1006/mthe.2002.0650
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of Feasibility of In Vivo Gene Therapy for Gaucher Disease Using a Chemically Induced Mouse Model

Abstract: Progress towards developing gene therapy for Gaucher disease has been hindered by the lack of an animal model. Here we describe a mouse model of Gaucher disease which has a chemically induced deficiency of glucocerebrosidase and that accumulates elevated levels of glucosylceramide (GL-1) in the lysosomes of Kupffer cells. Administration of mannose-terminated glucocerebrosidase (Cerezyme) resulted in the reduction of GL-1 levels in the livers of these animals. Gene transduction of hepatocytes with a plasmid DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 45 publications
1
40
0
Order By: Relevance
“…It is important to determine whether unmodified enzyme also localized to the Kupffer cells. Marshall et al [15] showed that unmodified GC has the ability to localize to Kupffer cells and exhibits a longer half life than the modified enzyme. The unmodified GC expressed by gene transfer could be a useful therapeutic for Gaucher patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to determine whether unmodified enzyme also localized to the Kupffer cells. Marshall et al [15] showed that unmodified GC has the ability to localize to Kupffer cells and exhibits a longer half life than the modified enzyme. The unmodified GC expressed by gene transfer could be a useful therapeutic for Gaucher patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, low transduction efficiency and poor long-term expression in these cells have hampered their clinical use [13,14]. Liver-targeted GC gene transfer using an adenovirus vector has demonstrated that enzyme secreted from transduced murine hepatocytes can reach tissues that are primarily affected [15]. This treatment, however, has immunological limitations.…”
mentioning
confidence: 99%
“…Marshall et al showed that GC produced by adenovirus vector-mediated gene transfer has the ability to localize to Kupffer cells and exhibits a longer half-life than the modified enzyme (Marshall et al 2002). The GC expressed by rAAVmediated gene transfer could be a useful therapeutic approach for patients with Gaucher disease.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation with Cerezyme, the wells were washed twice with PBS containing 1 mg/ml yeast mannan and twice more with PBS and then lysed in 1 ml of KP buffer as for the macrophages. Lysates were assayed for glucocerebrosidase activity using the artificial fluorogenic substrate 4-methylumbelliferyl-␤-D-glucopyranoside as described previously (Marshall et al, 2002). Protein levels were quantified using the MicroBCA protein assay kit (Pierce Chemical, Rockford, IL).…”
Section: Methodsmentioning
confidence: 99%